Growth and Neurodevelopmental Outcomes of Early, High‐Dose Parenteral Amino Acid Intake in Very Low Birth Weight Infants: A Randomized Controlled Trial. Issue 3 (12th December 2017) - Balakrishnan, Maya; Jennings, Alishia; Przystac, Lynn; Phornphutkul, Chanika; Tucker, Richard; Vohr, Betty; Stephens, Bonnie E.; Bliss, Joseph M.
Abstract: Background : Administration of high‐dose parenteral amino acids (AAs) to premature infants within hours of delivery is currently recommended. This study compared the effect of lower and higher AA administration starting close to birth on short‐term growth and neurodevelopmental outcomes at 18–24 months corrected gestational age (CGA). Methods : Infants <1250 g birth weight (n = 168) were randomly assigned in a blinded fashion to receive parenteral nutrition providing 1–2 g/kg/d AA and advancing daily by 0.5 g/kg/d to a goal of 4 g/kg/d (standard AA) or 3–4 g/kg/d and advancing to 4 g/kg/d by day 1. The primary outcome was neurodevelopmental outcomes measured by the Bayley Scales of Infant and Toddler Development, Third Edition at 18–24 months CGA. Secondary outcomes were growth parameters at 36 weeks CGA among infants surviving to hospital discharge, serum bicarbonate, serum urea nitrogen, creatinine, AA profiles in the first week of life, and incidence of major morbidities and mortality. Results : No differences in neurodevelopmental outcome were detected between the high and low AA groups. Infants in the high AA group had significantly lower mean weight, length, and head circumference percentiles than those in the standard AA group at 36 weeks CGA and at hospital discharge. These differences did not persist after controlling for birth growth parameters, except for head circumference. Infants in the high AA group had higher mean serum urea nitrogen than the standard group on each day throughout the first week. Conclusion : Current recommendations for high‐dose AA starting at birth are not associated with improved growth or neurodevelopmental outcomes.